Frequency-driven-multistable hazy states for smart windows with ultralow power consumption - J. W. Ryu; G. J. Choi; H. J. Jeon; Y. Choi; J. S. Gwag (APL Materials, 2024)
This study presents an ultralow-power smart window that uses frequency-driven electroconvection in a chiral liquid crystal (LC) to generate multiple stable haze states. Irradiating a chiral nematic LC mixture with ultraviolet light ionizes some LC molecules, activating electroconvection that causes dynamic light scattering. The haze state depends on frequency and voltage because of the mass and charge of the LC molecular ions. These parameters control the ratio of the focal-conic (haze) to the planar (transparent) states that arise when the voltage is removed. In particular, the applied frequency most strongly influences the distance through which the massive LC molecular ions can move during a one-half cycle. Notably, these states are considerably stable; thus, they exhibit a constant haze over a long period. Experimental results show that by varying the frequency at a constant voltage and, subsequently, removing the voltage, continuous and stable haze values can be obtained at each frequency and that each of these states maintains similar haze levels (within 2% variation) for >1 day. These findings indicate the possibility of creating ultralow-power smart windows using these frequency-driven, multistable haze states.